The Identifikasi Nilai Pendidikan Karakter dalam Bingkai Teks Proklamasi Kemerdekaan Republik Indonesia - Agus Budianto; Widiatmoko, Sigit; Afandi, Zainal; Pratama, Affilah Putra; Sasmita, Gusti Garnis (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
The importance of implementing education is an answer to various challenges in the development of science and technology which, either directly or indirectly, influences the morale of the nation's young generation today. The exploration of the value of character education can be traced in the history of the Indonesian nation, especially in the text of the proclamation of independence for the Republic of Indonesia. This research aims to identify the values ​​of national character education based on the text of the proclamation of independence of the Republic of Indonesia. In conducting research, researchers used a qualitative approach to explore in depth what character education values ​​can be taken from the text of the proclamation. The data sources were obtained through literature studies and distributing online questionnaires to UNP Kediri history education students who had completed the lecture material for the sub-chapter of Indonesian independence. Based on the results of data analysis, it can be concluded that the value of national character education based on the text of the proclamation of independence of the Republic of Indonesia includes unity and oneness, devotion to God Almighty, tolerance, struggle/perseverance, patriotism, democracy, human rights, independence, independence, nationalism and justice.